Flood detector - Emi Rahayu, Mat Noor (2008)
Flood is one of the biggest disaster which cause properties destruction and fatal. Lots of flash flood victims are not capable to save their important documents like their Identity Card (IC), birth certificate, etc. The problem caused by their unprepared and unexpected about having a flood especially in unconscious condition such as when they were sleeping. Flood Detector is a system that is designed to enable user to detect the critical water level before flood occurs. The flood detector is used to detect the critical water level before flood occurs. The system is designed so that the transmitter is mounted high on the wall and the flood sensor is placed in a location where flooding is possible. The entire system is composed of two modules, which is master module and slave module, separated by a distance. The master module will be a sending unit which will send data to the slave module via Bluetooth link, in order to inform the user about the status of water level and display the status of the flood level at the HyperTerminal at the personal computer. At the same time, the master module will produce an alarm signal and display the flood level by using three LED as water level indicator. With this flood detector, the user will be more alert if the flash floods occur by hearing the alarm signal even when they are sleeping. So, they have enough time to save their important properties and also can alert their neighbors about the flood which is about to occur and ask them to take the smart action. The user can estimate the critical time left or the total period to save their properties by looking at the water level indicator. This project is using a Microchip PIC16F877A microcontroller and focuses on Bluetooth technology. This system can be applied especially at area where flood is possible.